Disentangling competition, herbivory, and seasonal effects on young plants in newly restored communities - Parsons, Michael; Lamont, Byron; Koch, J.; Dods, K. (Blackwell Science Inc., 2007)
Optimizing techniques of impact and consequence assessment are critical when faced with the challenges of reclamation within a damaged or altered ecosystem. Much debate has arisen over an appropriate index to evaluate herbivore and competition effects on restored communities. We assessed concurrent environmental pressures by means of repeated measurements using three common indices of plant performance (biomass, shoot extension, and survival) in conjunction with monitoring for number and timing of plants eaten. Our design incorporated 24 species, representing a range of taxonomic groups andgrowth forms, planted at low and high densities, inside and outside large-scale mammal exclosures. We demonstrate that biomass and height measurements are correlated (at both the individual and the combined species levels), whereas the survival index often showed independent information. Using the most conservative measure (survival), we delineate between plant deaths attributed to seasonal effects, competition (some facilitation wasapparent), and herbivory (both compensation and loss of fitness were demonstrated). Plant spacing effects depended on the index (response variable) and whether we measured individual or combined species. The survival index rarely showed competition effects. Due to counter facilitation effects, competition was not demonstrated for any index at the combined species level. The comparison of the relative order and magnitude of plants being eaten against impact identified vulnerable and compensating species. Once identified, compensating species may be used sacrificially to buffer damage in new reclamation systems, whereas deterrents may be used around known vulnerable species.